Striatal Astrocytes Act as a Reservoir for L-DOPA - Asanuma, Masato (Public Library of Science, 2014)
L-DOPA is therapeutically efficacious in patients with Parkinson’s disease (PD), although dopamine (DA) neurons are severely degenerated. Since cortical astrocytes express neutral amino acid transporter (LAT) and DA transporter (DAT), the uptake and metabolism of L-DOPA and DA in striatal astrocytes may influence their availability in the dopaminergic system of PD. To assess possible L-DOPA- and DA-uptake and metabolic properties of striatal astrocytes, we examined the expression of L-DOPA, DA and DAT in striatal astrocytes of hemi-parkinsonian model rats after repeated L-DOPA administration, and measured the contents of L-DOPA, DA and their metabolite in primary cultured striatal astrocytes after L-DOPA/DA treatment. Repeated injections of L-DOPA induced apparent L-DOPA- and DA-immunoreactivities and marked expression of DAT in reactive astrocytes on the lesioned side of the striatum in hemi-parkinsonian rats. Exposure to DA for 4h significantly increased the levels of DA and its metabolite DOPAC in cultured striatal astrocytes. L-DOPA was also markedly increased in cultured striatal astrocytes after 4-h L-DOPA exposure, but DA was not detected 4 or 8h after L-DOPA treatment, despite the expression of aromatic amino acid decarboxylase in astrocytes. Furthermore, the intracellular level of L-DOPA in cultured striatal astrocytes decreased rapidly after removal of extracellular L-DOPA. The results suggest that DA uptaken into striatal astrocytes is rapidly metabolized and that striatal astrocytes act as a reservoir of L-DOPA that govern the uptake or release of L-DOPA depending on extracellular L-DOPA concentration, but are less capable of converting L-DOPA to DA.